The general form of First Order Equation

- $A{\frac {df(x)}{dx}}+Bf(x)=0$

Which can be writte as

- ${\frac {df(x)}{dx}}=-{\frac {B}{A}}f(x)$

has one root of the exponential function form

- $f(x)=Ae^{(}-{\frac {B}{A}})t$

Equation is an expression of one variable such that

- $A{\frac {df(x)}{dx}}+Bf(x)=0$
- ${\frac {df(x)}{dx}}+{\frac {B}{A}}f(x)=0$
- ${\frac {df(x)}{f(x)}}=-{\frac {B}{A}}dx$
- $\int {\frac {df(x)}{f(x)}}=-{\frac {B}{A}}\int dx$
- $Lnf(x)=-{\frac {B}{A}}t+C$
- $f(x)=e^{[}-{\frac {B}{A}}t+C]$
- $f(x)=e^{C}e^{(}-{\frac {B}{A}})t$
- $f(x)=Ae^{(}-{\frac {B}{A}})t$